Is online disclosure the key to corporate governance?. Issue 5 (9th September 2019) - López-Arceiz, Francisco J.; Torres, Lourdes; , Ana J. Bellostas
Abstract : Purpose: The economic literature shows contradictory results when the relationship between corporate governance and financial position is assessed. The purpose of this paper is to analyze the role of the online disclosure of information, as an omitted variable, in this relationship. Design/methodology/approach: In order to test the role of the online disclosure of information, a set of the structural equation models is evaluated. In these models, the indirect effect of the online disclosure on the relationship between corporate governance and the financial position, defined by performance, funding and investment, is analyzed. Findings: Using data from a sample of 252 Spanish public non-profits between 2012 and 2016, the authors found that the development of corporate governance practices is not, by itself, able to improve the financial position of these organizations. These improvements can only be achieved if the online disclosure is promoted. Research limitations/implications: Organizations should not only follow corporate governance practices but also communicate to the stakeholders the degree of development of these practices in an exercise of accountability. Finally, Web 3.0 practices must be promoted because they can be a mechanism to reinforce corporate governance practices and achieve a solid financial position. Originality/value: This study contributes to the debate about the role of the online disclosure, introducing this transparent practice as a variable omitted by previous research. Moreover, the authors have considered the evolution for a period of four years in relation to the information published by each organization on the internet.